Translanguaging practices amongst immigrant learners :implications for decolonised discourses - Dhokotera, Clarah (My University, 2019)
he purpose of this study was to explore how the immigrant learners show their linguistic resources in monolingual biased spaces and how the teacher’s monolingual bias practices impact on the multilingual immigrant learners. This was achieved through the examination of teacher practices and approaches in English and IsiZulu language lessons. The multilingual theories, the Translanguaging and Decolonial theories were discussed to ascertain how these theories can be of great value in multilingual immigrant learner spaces. Related literature points out that there is interdependence between languages and fluidity of linguistic boundaries. Because of linguistic fluidity, the crossing over of languages is a social language practice amongst multilinguals. It is therefore obsolete to treat languages as separate entities and fixed Makalela, (2015), Garcia (2018) and Kirarmba, (2016). At further examination, the theory (Decolonial) points out one language use in classrooms as a colonial language teaching practice, which is based on monolingual ideologies of one language policy A qualitative design was used in an ethnographic case study, and lessons observations in English and IsiZulu were done. The observation data were augmented by teacher and learners interviews and validation was with data from learners creative work documents. The data were collected from four teachers (two IsiZulu and two English) and eight purposively sampled multilingual immigrant learners. The findings revealed that immigrant learners have numerous linguistic, cultural, and semiotic resources and experiences that they may use in language classrooms for enhancing their language learning. However, the resources are being hindered by the monolingual practices and methodologies which are still dominant in many language classrooms. The study therefore recommends the enhancement of teacher expertise and Translanguaging techniques and decolonial strategies in language teaching.
A research report submitted to the School of Education, Faculty of Humanities University of the Witwatersrand in partial fulfilment of Master of Education in Applied Language and Literacy Studies, June 2019
Keywords: Immigrant children--Education; Translanguaging (Linguistics)